The Contribution of Legal Science to The Formation of Legal Norms in Indonesian Society: A Review from A Social Perspective - Kurdi, Kurdi; Prayoga, Sandi Yudha; Cahyo, Raul Gindo (ARBITER: Jurnal Ilmiah Magister Hukum, 2025)
Legal science has a very significant role in dealing with social dynamics by adjusting legal norms to remain relevant to the needs of a growing society. This study aims to explore the contribution of legal science in forming legal norms that are adaptive and responsive to social change, technology, and global values, while maintaining the basic principles of justice and humanity. The method used in this study is the normative juridical method, with a statutory and conceptual approach. The statutory regulatory approach is used to analyze existing regulations, while the conceptual approach is used to understand the legal theories underlying the formation of legal norms in Indonesia. The results of the study show that legal science not only reflects social change, but also plays an active role in formulating and updating legal norms by the development of the times, so as to be able to create a harmonious and just social order.